(untitled) (Journal of Pathology of Nepal, 2017)
Lymphomas of the orbit and orbital adnexae are rare tumors, comprising only 1% of all non-Hodgkin’s lymphoma. Lymphomas are the most common primary orbital tumor in adults of age 60 years and older. Here we present a case of 49 year male with left upper lid swelling since 1 year who was diagnosed histopathologically as non-Hodgkin’s lymphoma of orbital region.